Characterization of a local genetic sexing strain as well as a wild population of anopheles arabiensis from KwaZulu Natal, South Africa - Dandalo, Leonard Chikondi (My University, 2017)
Malaria remains endemic in the north-eastern areas of KwaZulu-Natal (KZN), Mpumalanga and Limpopo provinces of South Africa (SA). Anopheles arabiensis is now implicated as the main malaria vector. This vector is not completely amenable to current vector control strategies which target indoor biting and resting mosquitoes. SA is moving towards malaria elimination and there is a need for additional vector control interventions to complement existing tools. The sterile insect technique (SIT) targeting An. arabiensis was selected as a potential intervention. In a mosquito SIT programme, only sterile males should be released because females are potential disease vectors. In order to achieve male releases only, a reliable sex separation strategy is needed. Additionally, it is imperative to gather entomological baseline information on the population density, species composition, and vectorial capacity of the targeted wild population. The aim of this study was to evaluate the use of a local genetic sexing strain for SIT and to determine the population dynamics of wild An. arabiensis in northern KZN. The following objectives were initiated in this study: development of a local genetic sexing strain (GSS), evaluation of the life history and reproductive effects of irradiation on An. arabiensis, and weekly mosquito surveillance was conducted over a period of 24 months. A local GSS named GMK was established by introgressing a local wild-type population of An. arabiensis with an available GSS strain. The strain exhibited the following attributes: low egg hatch rates, fast developmental time, long adult survival and a high mating competitiveness. Dieldrin treatment of GMK eggs/larvae mainly produced males but this result remains controversial. The irradiation dose of 70 Gy induced male sterility without compromising their mating competitiveness and impacted negatively on female fitness, but not vectorial capacity. The perennial presence of An. arabiensis, the dominant anopheline species in Mamfene, was confirmed. Its population density fluctuated with season reaching a peak in summer. Clay pots were more productive than the other collection methods, collecting 16.3 mosquitoes per trap. This study recorded for the first time wild caught An. arabiensis and An. vaneedeni infected with P. falciparum in SA. An arabiensis sporozoite infection rates were 0.7% (2014) and 0.5% (2015). Anopheles vaneedeni has never been implicated as a malaria vector in nature. However, an infection rate of 1.96% was recorded (2014-2015), which implicate this species as a potential malaria vector. These results highlight the importance of intensive mosquito surveillance to establish malaria vectors responsible for low level/residual malaria transmission. The data generated provides important baseline vector surveillance information and is valuable to stakeholders and researchers to make informed decisions regarding the use of SIT against vector mosquitoes in SA.
Thesis submitted to the Faculty of Health Science, University of the Witwatersrand, in fulfilment of the requirements for the degree of Doctor of Philosophy. Johannesburg, 2017
Keywords: Anopheles arabiensis; Malaria